PENERAPAN PROFIT DISTRIBUTION PADA PERBANKAN SYARIAH: ADIL DALAM SITUASI PANDEMIC COVID 19 - Asiyah, Binti Nur; Pratiwi, Yanuar Mila; Nuroniyyah, Fathiyyatun; Natory, Dimas Asyif (Institut Agama Islam Negeri (IAIN) Ternate, 2021)
Profit Distribution or profit sharing distribution basically has two principles that are rofit sharing and revenue rharing. Fatwa of the National Sharia Council concerning the principle of distribution of operating results with the principle of revenue sharing to emphasize on sharia financial institutions. This principle provides benefit (al-ashlah), justice in any situation. This paper is written with a qualitative approach and the type of research is a literature study. The analysis was carried out descriptively on the results of the data obtained. The results of this paper include, among others, in the COVID-19 pandemic situation, revenue-sharing for Islamic banking has decreased, from the total profit-sharing financing distributed by Islamic banks, it tends to increase. This shows a form of justice for Islamic banks in providing a profit burden to customers when their income achievement is affected by COVID-19.